Social participation of stroke patients: a bibliometric analysis - Yan, Jiaqing; Wang, Yancheng; Zhang, Liang; Chen, Ping; Yang, Nini; Zhang, Hongbo (Frontiers in Neurology, 2025)
ObjectiveResearch on social functioning rehabilitation in stroke patients has received significant attention. In this study, we performed a bibliometric analysis using CiteSpace to examine publications focuses on post-stroke social participation between 2000 and 2025.MethodsLiterature related to social participation of stroke patients was retrieved from the Web of Science Core Collection from January 1, 2000, to March 28, 2025, and the number of articles, countries, institutions, authors, references, and keywords were visualized and analyzed using Microsoft Office Excel and CiteSpace software.ResultsThe final analysis included836 publications, demonstrating a steady increase in annual publications over the 25-year period. Among contributing authors, Ng, Shamay S. M. demonstrated the highest productivity (20 publications). The United States and La Trobe University were the leading contributing countries and institutions. “Archives of Physical Medicine and Rehabilitation” was the most influential journal with a total of 600 citations (impact factor 3.6 in 2024). High-frequency keywords include “social participation,” “quality of life,” and “community integration.”ConclusionThis 25-year bibliometric analysis of post-stroke social participation research identifies priority areas for future studies.